Benign Intracranial Hypertension with Nasal Steroid - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
A 13 year-old boy with Crohn's disease (in remission) was evaluated at the Department of Ophthalmology, University Hospital, Nottingham, UK, because of a 10 day history of head and back pain, intermittent blurring of vision, and squint.